Geography and the theory of uneven and combined development: Theorizing uniqueness and the return of China. (August 2021) - Dunford, Michael; Gao, Boyang; Liu, Weidong
As societal interaction and combination play a vital role in shaping spatio-temporal development paths, meta-theories of uneven development should give way to a relational meta-theory of uneven and combined development (U&CD). U&CD examines at multiple levels of abstraction not just internal causal mechanisms governing the trajectories of individual societies but also causal mechanisms deriving from societal interaction in a world of multiple unevenly developed societies and multiple development pathways. As a consequence it helps explain geographical differentiation and the multiplicity, hybridity and multilinearity of processes of development. As U&CD examines the roles of ideal and efficient causes and causal laws, it also entails revitalized social science and political economy approaches in geography and urban and regional development studies. To demonstrate the indispensability of analyses of the role of societal interaction and the explanatory significance of the theory of U&CD, a series of longue-durée vignettes explore their role in explanations of the spatio-temporality of the decline and subsequent return of China in a changing and interdependent world.